2019
DOI: 10.1038/s41598-019-52095-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlated impurity complex in the asymmetric tunneling contact: an ideal system to observe negative tunneling conductivity

Abstract: We studied theoretically electron transport through the impurity complex localized between the tunneling contact leads by means of the generalized Keldysh diagram technique. The formation of multiple well pronounced regions with negative tunneling conductivity in the I-V characteristics was revealed. The appearance of negative tunneling conductivity is caused by the presence of both strong Coulomb correlations and the asymmetry of tunneling rates, which lead to the blockade of the electron transport through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In the case of large Coulomb interaction Green’s functions look as 57 Section 3 of the Supplementary Material shows how to calculate nonequilibrium occupation numbers and for the impurity atoms states. Using expressions ( 13 ) and ( 16 ) one can calculate tunneling conductance in the presence of strong Coulomb interaction.…”
Section: The Role Of Coulomb Interactionmentioning
confidence: 99%
“…In the case of large Coulomb interaction Green’s functions look as 57 Section 3 of the Supplementary Material shows how to calculate nonequilibrium occupation numbers and for the impurity atoms states. Using expressions ( 13 ) and ( 16 ) one can calculate tunneling conductance in the presence of strong Coulomb interaction.…”
Section: The Role Of Coulomb Interactionmentioning
confidence: 99%
“…The negative tunneling conductivity has been studied both experimentally 67 69 and also theoretically 70 , 71 . The recent work by Masolva et al 72 has demonstrated that the interplay between Coulomb correlations and the asymmetry in tunneling rates gives rise to negative tunneling conductivity.…”
Section: Introductionmentioning
confidence: 99%